The Microstructure Testing of Brass Materials on the Liquified Petroleum Gas (LPG) Gas Valve - Muhamad Emiriza; Winda Sri Jaman; Nur Ichsan Sumardani; WS Mada Sanjaya (Risenologi, 2021)
In this study brass used as a sample is brass which is used as a raw material for LPG (Liquified Petroleum Gas) valves. Two samples were taken which were prepared before the composition test and microstructure test. From the results of the micro test, it is found that the brass phase structure is the ? proeutectic phase and the ? phase. The proeutectic phase ? has an FCC structure while the ? phase has a BCC structure. There are also black dots which are Lead with different percentages for each sample.Lead tends to be in the particle-shapedside.